Factors affecting survival potential of Gliocladium virens in soil - SITANSU PAN, D.K. SAHA and (Indian Phytopathology, 2002)
A highly antagonistic isolate of Gliocladium virens (15 GV 1 , B. No. 4359, IARI) was studied in respect of its survival ability in soils of three different pH (5.6, 7.0 and 8.0). In red laterite soil of Purulia (pH 5.6) except in air dry soil and incubation temperature at 40°C, population as a function of incubation period increased upto 21 days  irrespective of soil moisture and incubation temperature and declined thereafter. "The rate of decrease was more affected by moisture condition of the soil than that of temperature. The rate of decrease in population of the antagonist was very sharp in soil with 25% moisture and increase in population was more in soil with 50% moisture. The population irrespective of the pH of soils disappeared earlier within 30-60 days specially in air dry soil at 30°C while in soils of other moisture levels, the survival of spore was longer (Ca 105-150 days). In air dry soil at pH 8.0 the population began to cut down after 15 days while in other moisture levels after 21 days. In general, 40°C appeared lethal for survival of the antagonist in soils of three different pH regardless of the moisture levels of soil.